Mechanism for epeirogenic uplift of the Archean Dharwar craton, southern India as evidenced by orthogonal seismic reflection profiles - Biswajit Mandal (Nature Portfolio, 2021)
Abstract Plateaus, located far away from the plate boundaries, play an important role in understanding the deep-rooted geological processes responsible for the epeirogenic uplift and dynamics of the plate interior. The Karnataka plateau located in the Dharwar craton, southern India, is a classic example for the plateau uplift. It is explored using orthogonal deep crustal seismic reflection studies, and a mechanism for the epeirogenic uplift is suggested. A pseudo three-dimensional crustal structure derived from these studies suggests a regionally extensive 10 km thick magmatic underplating in the region. It is further constrained from active-source refraction and passive-source seismological data. We interpret the Marion and Reunion mantle plume activities during 88 Ma and 65 Ma on the western part of Dharwar craton are responsible for the magmatic underplating, which caused epeirogenic uplift. Flexural isostasy related to the onshore denudational unloading and offshore sediment loading is also responsible for the persisting uplift in the region. Plate boundary forces are found to be contributing to the plateau uplift. The present study provides a relationship between the mantle plumes, rifting, development of continental margins, plateau uplift, and denudational isostasy. Combination of exogenic and endogenic processes are responsible for the plateau uplift in the region.